2014
DOI: 10.1039/c4ay00255e
|View full text |Cite
|
Sign up to set email alerts
|

Electroanalytical determination of bumetanide employing a biomimetic sensor for detection of doping in sports

Abstract: This paper describes the development of a new method for the quantification of bumetanide in urine samples from athletes and in pharmaceutical formulations to detect doping, using a biomimetic sensor based on a biomimetic catalyst of the P450 enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…A comparison of the electroanalytical methods reported in the literature for the determination of BMT is summarized in Table 1. From these data, it is possible to conclude that our method presents better performance in relation to the linear response and detection limits in agreement with other voltammetric methods found in the literature [13,34].…”
Section: Electroanalytical Determination Of Bmtsupporting
confidence: 89%
See 1 more Smart Citation
“…A comparison of the electroanalytical methods reported in the literature for the determination of BMT is summarized in Table 1. From these data, it is possible to conclude that our method presents better performance in relation to the linear response and detection limits in agreement with other voltammetric methods found in the literature [13,34].…”
Section: Electroanalytical Determination Of Bmtsupporting
confidence: 89%
“…The authors indicated that the complex promotes electrocatalysis of BMT Electronic supplementary material The online version of this article (doi:10.1007/s00604-017-2443-5) contains supplementary material, which is available to authorized users. reaching a limit of quantification of 9.0 × 10 −7 mol L −1 [13]. Nevertheless, the most of these studies have limited linear region and higher detection limit than required for determination of BMT in urine.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, BUM inhibits the chloride cotransporter NKCCl (cation‐chloride cotransporter) to maintain steady intracellular (Cl − ) levels in neurons (Greger & Wangemann, 1987; Löscher & Kaila, 2022; Zhao et al, 2022). There are many ways to analyze BUM in various biological matrices, either on their own (Bökens et al, 1988; Legorburu et al, 2001; Walmsley et al, 1981; Wells et al, 1991) or in conjunction with other diuretics for anti‐doping studies (dos Santos Ruy et al, 2014; Li et al, 2011; Luiz et al, 2019), employing a variety of techniques such as the fluorimetric and high‐performance liquid chromatography (HPLC) methods (Howlett et al, 1984). However, these methods have some inherent disadvantages, including the need for many solvents; the difficulty in validating them on a laboratory scale; laborious separation, derivatization, or incubation procedures; the necessity for large samples; and their lack of sensitivity or specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Molecularly imprinted technology produces porous materials with specific recognition sites with the ability to preferably bind to the desired analyte, thereby improving the efficiency in the solid-phase extraction step [27,28]. Compared to other selective sorbents, MIPs demonstrate high mechanical strength, and high thermal and chemical stability, enabling their applicability in a variety of chemical environments [29][30][31][32]. Due to these advantages, MIPs represented a great advance in the field of sample preparation, acting as stationary phases in affinity chromatography [33] and as sorbent in solid-phase extraction [34].…”
Section: Introductionmentioning
confidence: 99%